Pemanfaatan Teknologi Virtual Reality (VR) Dalam Pembelajaran Pada Lembaga Kursus Dan Pelatihan Rumah Tik Labuhanbatu - Ernawati, Andi; Sitorus, Zulham; Wijaya, Rian Farta; Aulia, Ananda; Siregar, Andree Risky Yuliansyah; Sofyan, Siti Nurhaliza (HIMPUNAN DOSEN GEMILANG INDONESIA, 2024)
Learning using technology continues to develop along with developments in technology itself. One technology that is increasingly being used in learning is virtual reality (VR). Virtual Reality is a technology that produces a digital environment that resembles the real world and allows users to interact with that environment. Including in Labuhanbatu Regency, where virtual reality media has been used as a learning medium. However, if we observe that the use of virtual reality as a learning medium has not been distributed thoroughly to every level of student, only the student level can access learning using virtual reality. And if we look more deeply, the virtual reality media content that is presented is able to improve the quality of student learning for each level because virtual reality media will really help improve the imagination and mindset of students at all levels to become more effective and efficient. In Labuhanbatu Regency there are many course and training institutions, judging from the area and the number of course and training institutions in Labuhanbatu Regency, the introduction of virtual reality learning media in Labuhanbatu Regency should be managed generally for all levels of students as a basis for community service activities (PKM). . This activity aims to provide training to students in Labuhanbatu Regency about learning methods using virtual reality technology through videos on cellphones using the Millea Lab Viewer application and VR Player with a virtual box device. Activities carried out focus on introducing and training virtual reality for learning. The methods used include training for students at all levels at the Labuhanbatu Tik House course and training institution regarding the features and concepts of virtual reality, the goals, benefits and practices of using virtual reality. After attending the training, students at the Tik Labuhabatu home course and training institution experienced an increase in their knowledge about virtual reality, as well as their ability to improve the quality and creative imagination in learning virtual reality media content in Labuhanbatu Regency Keywords: virtual reality; learning; content, lkprumahtik, Labuhanbatu